Chitotriosidase attenuates brain inflammation via HDAC3/NF-κB pathway in D-galactose and aluminum-induced rat model with cognitive impairments. (November 2021) - Yu, Xingyan; Yu, Weihua; Wu, Lihua; Yang, Wenkai; Lü, Yang
Highlights: CHIT1 regulates brain inflammation via HDAC3/NF-κB p65 pathway, contributing to improvement of cognitive impairment. CHIT1 skews polarization from a pro-inflammatory environment toward an anti-inflammatory one. CHIT1 has a potential therapeutic value in AD via modulation of inflammation. Abstract: Chitotriosidase (CHIT1, chitinase 1) is increased in the cerebrospinal fluid and peripheral blood of Alzheimer's disease (AD) patients. Our previous study has shown that CHIT1 provides potential protection through microglial polarization and reduction of β-amyloid (Aβ) oligomers on rat models of AD. Histone deacetylase 3 (HDAC3) plays a significant role in the expression and regulation of proteins related to the pathophysiology of AD. In addition, nuclear factor-kappa B (NF-κB) signaling pathway activation in neurons is associated with the progression of AD. NF-κB activation is regulated by HDAC3 deacetylation. In the present study, we researched the role of CHIT1 in HDAC3/NF-κB signaling in D-galactose (D-gal) and aluminum-exposed rat model with cognitive impairments. Following CHIT1 treatment, we found that the protein and mRNA levels of HDAC3 and NF-κB were reduced, the expression level of IκBα increased, anti-inflammatory factors (Arg-1, IL-10, and CD206) were elevated while pro-inflammatory factors (TNF-a, iNOS, and IL-1β) were decreased in D-gal/aluminum-induced AD rats. These results indicate that CHIT1 can regulate brain inflammation via HDAC3/NF-κB p65 pathway, contributing to improvement of cognitive impairment.